Digitalization and Diglossia: Assessing the Effectiveness of Arabic as a Tool of Public Diplomacy in the Digital Era - Akhmad Fadhillah Kartono; Abd. Rahim; Dian Malinda; Ansar (Journal of Digital Arabic Language Education, 2026)
This article examines the urgency and transformation of Arabic language digitalization in strengthening public diplomacy (soft power) and facilitating cross-cultural communication in the era of digital disruption. Arabic, with more than 400 million speakers and its status as one of the six official languages of the United Nations, is no longer understood merely as an instrument of religious ritual but has evolved into a strategic medium within international geopolitical discourse. Nevertheless, a striking paradox emerges: although the number of Arabic-speaking internet users has grown rapidly since the early 2000s, the proportion of Arabic-language content in the global digital sphere remains far behind, with various estimates placing it at only 1 to 5 percent of total web content worldwide. Employing a descriptive-analytical qualitative method grounded in systematic library research of 20 primary and secondary sources published between 2004 and 2026, this study analyzes three aspects: (1) the role of digital technology and artificial intelligence in strengthening the Arab world's public diplomacy, (2) the contribution of digitalization to more inclusive cross-cultural communication, and (3) the structural challenges hindering the optimization of this role. The findings indicate that the use of digital platforms, Arabic-language media such as Al Jazeera, and Natural Language Processing (NLP) technology has expanded the reach of narratives and intercivilizational dialogue; however, their effectiveness remains constrained by the digital content gap and linguistic complexity arising from the diglossia between Fusha (Modern Standard Arabic) and Ammiyah (colloquial dialects). This article recommends strengthening cross-sector collaboration among governments, academics, and technology developers to address this gap.